Aberrant palatal exostosis - Thalles Moreira Suassuna; Jéssica da Silva Cunha; Nathalie Murielly Rolim de Abreu; Fábio Correia Sampaio (Editorial Ciencias Médicas, 2020)
Introduction: Exostosis is a benign bone growth that commonly affects the jaw and maxilla, but is rarely large. Objective: To describe a case of rare palatal exostosis and discuss the main clinical aspects involved. Case presentation: A case is presented of a male 66-year-old dark-skin patient with a history of hard palate enlargement of an indefinite time of evolution, and chewing and phonation disorders. The lesions had obliterated the entire palatal depth and occupied a large section of the oral cavity. Cone beam computed tomography revealed corticalized areas on the surface of the lesion and less hyperdense central areas compatible with mature bone marrow. After preoperative examination and advice, the patient underwent surgical treatment under general anesthesia to remove the bone mass and underlying osteoplasty to obtain normal palatal contours. The material collected was sent for biopsy testing, which established the diagnosis of exostosis. The patient recovered without any complications. Conclusions: Although exostosis is a benign bone growth, in this case it caused functional problems to the patient, thus requiring surgical treatment. Three months after removal, the disorders have been reverted to normal and prosthetic rehabilitation is underway.